2011
DOI: 10.21608/jpp.2011.85469
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity Associated With Agronomic Traits and Biotic Stresses Using SSR Markers in Some Egyptian Rice Genotypes

Abstract: Genetic diversity underlies the improvement of crops by plant breeding. In Egypt, pedigree analyses indicate that the rice varieties currently under cultivation are closely related in there genetic background. Effective breeding programs, based on the information about of the genetic diversity of cultivars, are needed to broaden the genetic bases of local rice germplasm in the country. The present study has been conducted to evaluate the pattern, type and extent of genetic variability and relatedness among som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…This fungus caused many high yielding varietal breakdown with the high rate of mutation, race shifting and change of dominant specific races on susceptible cultivars as Sakha101 and Sakha104breakdown (Khush andJena, 2009, El-Shafey et al 2015). Broadening the genetic background of new promising lines should utilize a wide range of diversity and new resources of blast resistance (El-Refaee et al 2011). Brown spot disease caused by Bipolaris oryzae is common in poor soils, bad drainage system, low water quality and saline soil.…”
Section: Indroductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This fungus caused many high yielding varietal breakdown with the high rate of mutation, race shifting and change of dominant specific races on susceptible cultivars as Sakha101 and Sakha104breakdown (Khush andJena, 2009, El-Shafey et al 2015). Broadening the genetic background of new promising lines should utilize a wide range of diversity and new resources of blast resistance (El-Refaee et al 2011). Brown spot disease caused by Bipolaris oryzae is common in poor soils, bad drainage system, low water quality and saline soil.…”
Section: Indroductionmentioning
confidence: 99%
“…In addition, EL-Shafey et al, (2015) they found that cultivars, Giza 177, Giza 178, still record complete resistance and some promising lines as full matching with current results. So, these varieties could be used as resistant resources to broaden the genetic background (El-Refaee, 2011).…”
Section: Race Identification Of Rice Blast Populationsmentioning
confidence: 99%